TRNA modifications: Necessary for correct tRNA‐derived fragments during the recovery from stress?. (11th January 2013) - Durdevic, Zeljko; Schaefer, Matthias
<x xml:space="preserve">Abstract</x> Endonuclease‐mediated tRNA fragmentation has been observed in many species suggesting functional importance for tRNA fragments. The size distribution of tRNA‐derived fragments indicates the existence of mechanisms that protect tRNAs and their fragments from total degradation by exonucleases. Could post‐transcriptional modifications be important for the controlled processing of tRNAs? <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>